The Use of SLiMS in the Processing of Library Materials at Elementary School Library - Hotimah, Ananda Husnul; Rukmana, Evi Nursanti; Rohman, Asep Saeful (Edulib, 2022)
The application of information technology in the library comes along with the development of human culture itself. The application of IT in libraries can function in various forms, including as a library management system that can be integrated with a library management system. Senayan Library Management System or Senayan or SLiMS is software that handles free library management with open source code. SLiMS has various features, such as Online Public Access Catalog (OPAC), digital content/files, Bibliography/catalog database management, integrated catalog creation, serial publication control, integrated search engine creation, document item management with barcode support, master file management and support circulation. This study aims to see the benefits of using SLiMS in processing library materials at the State Elementary School of Jurumudi 1 Library. The research was conducted using a qualitative approach through case studies in the field. Data collection techniques include observation, interviews, literature, and document study. The results indicate that SLiMS facilitates the processing of library materials in SDN Jurumudi 1. The use of SLiMS speeds up the processing of library materials compared to conventional systems.